The 2-generator restricted burnside group of exponent 7 - O'Brien, E; Vaughan-Lee, M (2002)
We report on our construction of a power-commutator presentation for R(2, 7), the largest finite 2-generator group of exponent 7. Our calculations show that R(2, 7) has order 720416, nilpotency class 28, and derived length 5. The calculations also imply that the associated Lie ring of R(2, 7) satisfies relations which are not consequences of the multilinear identities which hold in the associated Lie rings of groups of exponent 7.